Outcomes of early oral feeding compared to delayed feeding in children after elective distal bowel anastomosis - T K Jayakumar; Kirtikumar J Rathod; Bala Eradi; Arvind Sinha (Wolters Kluwer Medknow Publications, 2023)
Background: Conventionally, oral feeds after distal bowel anastomosis surgery (ileostomy/colostomy closure) are delayed until after bowel peristalsis is established. The safety of an early feeding regimen is not established in children. This study compared early feeding regimens with delayed feeding in children undergoing elective intestinal anastomosis surgeries. Materials and Methods: In this retrospective multicentric cohort study, children undergoing elective distal bowel anastomosis surgery were divided into Group A (oral feeds allowed within 6 h) and Group B (delayed feeds). The two groups were compared for the incidence of abdomen distension, vomiting, surgical site infection, duration of analgesia, length of hospital stay, and readmission rate. Results: During the study, 58 patients were included: Group A (n = 26) and Group B (n = 32). The duration of analgesia (1.9 vs. 4.01 days) and length of hospital stay (3.38 vs. 5.0 days) were significantly less in Group A. Abdominal distension (7.7% vs. 15.6%), vomiting (11.5% vs. 15.6%), surgical site infection rate (3.8% vs. 12.5%), and readmissions (0% vs. 3.1%) were less in Group A, but statistically not significant. Conclusion: Early feeding after the elective restoration of distal bowel continuity can be safely practiced in the pediatric population. It is associated with a reduced need for analgesia and shorter hospital stay.